تعليم الصرف بمدرسة تأديب الشاكرين الإسلامية _ ميدان (دراسة وصفية تقويمية - zulpina zulpina (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
Abstract: This study aims to describe the application of Sharaf material in Arabic Language Learning, which is carried out at the Islamic Boarding School Ta'dib Asy-syakirin in Medan, with a qualitative research approach. The research data were obtained by using triangulation techniques through observation, interviews, and document study. This study will describe how Student Mastery in Understanding Sharaf material and the methods used in learning. The results showed that the Students' Mastery in Understanding Formulas of Tashrif at the Islamic Boarding School Ta'dib Asy-syakirin in Medan was not good due to several inhibiting factors either coming from students, teachers, or the school itself. While the composition of the sharaf material itself is very good and continuous from the first level to the next level. While the method used is the method of memorizing while singing. مستخلص البحث: تهدف هذه الدراسة الى وصف تطبيق مادة الصرف في تعليم اللغة العربية، والتي يتم تنفيذها بمدرسة التأديب الشاكرين الإسلامية ميدان ، مع منهج البحث النوعي. تم الحصول على بيانات البحث باستخدام تقنيات التثليث من خلال الملاحظة والمقابلات ودراسة الوثائق. ستصف هذه الدراسة كيفية إتقان الطالب في فهم مادة الصرف والطرق المستخدمة في التعلم. أظهرت النتائج أن إتقان الطلاب في فهم أوزان التصريف بمدرسة التأديب الشاكرين الإسلامية ميدان لم يكن جيدًا بسبب عدة عوامل مثبطة سواء من الطلاب أو المعلمين أو المدرسة نفسها. في حين أن تكوين مادة الصرف نفسها جيدة جدًا ومستمرة من المستوى الأول إلى المستوى التالي. بينما الطريقة المستخدمة هي طريقة الحفظ أثناء الغناء. Keywords: Application of Sharaf; Material of sharaf; Arabic Learningالكلمات المفتاحية: تطبيق الصرف، مادة الصرف، تعليم اللغة العربية